STRATEGI PEMASARAN PT. TWC DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DAN LABA USAHA PENGELOLAAN CANDI BOROBUDUR, PRAMBANAN DAN RATU BOKO - Yulianto, Atun (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2015)
PT. Taman Wisata Candi (TWC) is a form of concern the government to maintain and preserve the cultural and historical heritage in the form of temples Borobudur, Prambanan&RatuBoko palace. As a profit-oriented Limited Liability Company , evaluation is needed to measure the performance of the company as part of accountability to stakeholders. In this paper the subject focuses on the analysis of the implementation of the company’s marketing strategy in increasing the number of visits and business profit. Therefore, the research method used is descriptive qualitative backed quantitative data. The results showed that marketing st rategy of ‘low cost high impact’ applied by the company in 2014 through increased penetration of the domestic market, foreign market development, increase awareness of domestic market, development of services and creation of new tourism products resulted in an increase in the number of visitors 2.8% and operating profit 10.4% from the previous year. While cost efficiency (low cost) in 2014 yet to show maximum results, because the increase in the cost of direct as big as 45,9% is not significant with the company’s operating profit increase as big as 10.4%. In this case the increase in direct operating costs is greater rather than increase in the amount of corporation profits and followed by a decrease in the liquidity of the company with the current ratio is smaller than the previous year. Keywords: Marketing strategy,Operating profit, Visitor